Rural Mortality from External Causes in Russian Regions - Tatiana Blinova (European Regional Science Association (ERSA), 2014)
The paper addresses the factors that affect the reduction of rural mortality from external causes in the regions of RF of different types and contains an estimation of the degree of their impact. We made a quantitative analysis and built models of the factors and determinants of the existing interregional differences in the pattern of rural mortality from external causes of death (road traffic accidents of all kinds, accidental alcohol poisoning, murder and suicide). The paper presents the results of the study of the dynamics and pattern of external causes of rural mortality with the use of Rosstat's data for Russian regions (2000-2012), and describes the nosological, gender and regional profile of rural mortality from external causes. We also identified the social problem, which is a steadily high rate of mortality from external causes in a certain group of regions. We found that the impact of federal social policies on the reduction of rural mortality from external causes is asymmetric in the regions of different types. On the basis of our cluster analysis we developed taxonomy of Russian regions according to the pattern of external causes of rural mortality, formed seven groups of Russian regions and characterized them. The hypotheses were statistically tested by making a correlation, regression and factor analyses. We estimated the regression models that had been constructed for Russia in general and for two types of regions (with the highest and the lowest mortality from external causes) separately and included economic, social and behavioral explanatory variables, which made it possible to identify the determinants of rural mortality from external causes and describe their spatial combinations. The results of the analysis and modeling of spatial differences in the pattern of external causes of rural mortality can be used when developing regional programs for reducing mortality from external causes of death. This study is supported by the Russian Foundation for Basic Research (project # 12-06-00012).
Keywords: R1; J1; I1; 330; Russian regions; rural population; mortality; external causes; taxonomy; regression analysis; regional data; determinants; social policy